(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In the last year, the number of patients with autoimmune diseases has increased, due to the general “aging of the population, the number of elderly patients is increasing, representing the main circle of people regularly taking NSAIDs among them.